Lysosome-targeted multifunctional lipid probes reveal the sterol transporter NPC1 as a sphingosine interactor - Juarez Altuzar, Janathan Michael; Notbohm, Judith; Stein, Frank; Haberkant, Per; Hempelmann, Pia; Heybrock, Saskia; Worsch, Jutta; Saftig, Paul; Höglinger, Doris (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Lysosomes are catabolic organelles involved in macromolecular digestion, and their dysfunction is associated with pathologies ranging from lysosomal storage disorders to common neurodegenerative diseases, many of which have lipid accumulation phenotypes. The mechanism of lipid efflux from lysosomes is well understood for cholesterol, while the export of other lipids, particularly sphingosine, is less well studied. To overcome this knowledge gap, we have developed functionalized sphingosine and cholesterol probes that allow us to follow their metabolism, protein interactions, and their subcellular localization. These probes feature a modified cage group for lysosomal targeting and controlled release of the active lipids with high temporal precision. An additional photocrosslinkable group allowed for the discovery of lysosomal interactors for both sphingosine and cholesterol. In this way, we found that two lysosomal cholesterol transporters, NPC1 and to a lesser extent LIMP-2/SCARB2, bind to sphingosine and showed that their absence leads to lysosomal sphingosine accumulation which hints at a sphingosine transport role of both proteins. Furthermore, artificial elevation of lysosomal sphingosine levels impaired cholesterol efflux, consistent with sphingosine and cholesterol sharing a common export mechanism.